Entrepreneurship in Russia and China: The Impact of Formal Institutional Voids - Puffer, Sheila M.; McCarthy, Daniel J.; Boisot, Max (Entrepreneurship Theory and Practice, 2010)
Transition economies are often characterized by underdeveloped formal institutions, often resulting in an unstable environment and creating a void usually filled by informal ones. Entrepreneurs in transition environments thus face more uncertainty and risk than those in more developed economies. This article examines the relationship of institutions and entrepreneurship in Russia and China in the context of institutional theory by analyzing private property as a formal institution, as well as trust and blat/ guanxi as informal institutions. This article thus contributes to the literature on entrepreneurship and institutional theory by focusing on these topics in transition economies, and by emphasizing how their relationship differs from that in developed economies. We conclude that full convergence toward entrepreneurs‘ reliance on formal institutions may not readily occur in countries like Russia and China due to the embeddedness of informal institutions. Instead, such countries and their entrepreneurs may develop unique balances between informal and formal institutions that better fit their circumstances. Implications for the theory and practice of entrepreneurship in such environments are also offered.